Latar Belakang Pendidikan CEO, Pengalaman CEO dan Kinerja Perusahaan (Studi Pada Perusahaan yang Terdaftar di Indeks LQ45, Indonesia) - Abimanyu, I Wayan Pradnya Sena; Nugraha, Adri Putra (Ekonomis: Journal of Economics and Business, 2024)
This study aims to determine the effect of the CEO expertise (with the proxies of educational background and experience) on company performance (with the proxies of return on assets (ROA), return on equity (ROE), and dividend payout ratio (DPR)). This study employs quantitative method, in which the data are analyzed by multiple linear regression. The samples include companies listed in the LQ45 index of the Indonesia Stock Exchange for the 2016-2019 period. The results of the study exhibit that the CEO educational background affects ROA and ROE, except DPR. It is suggested that further studies consider not only educational background and experience but also work relations and gender, and use other performance assessment indicators such as PBV.